Penetapan dan Penerapan Peraturan Spesifik untuk Meningkatkan Kedisiplinan Siswa Kelas VIII SMP ABC Cikarang [Making and Applying Specific Rules for Hand Raising Before Speaking to Improve Discipline of Grade VIII Students at a Junior High School during Biology Class] - Eimenina Saemara Pelawi; Juniriang Zendrato; Lastiar Roselyna Sitompul (Polyglot, 2016)
It was discovered that during the process of learning biology, grade VIII students at SMP ABC in Cikarang lacked discipline which distrupted the ability of the class to study conducively.  To solve this problem, the researcher implemented a specific rule which was "Raise Your Hand before Speaking". The research aim was to see whether the discipline of the students in grade VIII could be improved through the establish and implementation of this specific rule. The method used was the classroom action research method. It used the cycle model and it was made reflectively. The research was completed after 2 cycles with 25 students as the subject of the research. The results of the data were analyzed using descriptive statistical techniques and descriptive qualitative. The instruments used to collect data were student questionnaires, observation sheets of students' discipline, student interview sheets, mentor’s feedback sheets and the researcher’s journal reflections. The data from all the instruments showed that in the second cycle the discipline indicators achieved a very good criteria. This shows that the establishment and implementation of the specific "Raise Your Hand Before Speaking" rule can improve the discipline of the students of grade VIII at SMP ABC in Cikarang. BAHASA INDONESIA ABSTRAK: Selama pembelajaran Biologi berlangsung ditemukan bahwa siswa kelas VIII SMP ABC CIKARANG kurang disiplin sehingga mengganggu terciptanya iklim kelas yang kondusif untuk belajar. Dalam rangka mengatasi masalah yang ditemukan, peneliti menerapkan peraturan spesifik Raise Your Hand before Speaking. Penelitian ini bertujuan untuk melihat apakah kedisplinan siswa kelas VIII dapat ditingkatkan melalui penetapan dan penerapan peraturan spesifik ini.Metodologi penelitian yang digunakan dalam penelitian ini adalah metode Penelitian Tindakan Kelas model siklus yang dilakukan secara bersiklus dan bersifat reflektif. Penelitian ini diselesaikan dalam dua siklus. Satu siklus terdiri dari dua pertemuan belajar. Subjek penelitian berjumlah 25 siswa.Hasil data dianalisa dengan menggunakan teknik statistik deskriptif dan deskriptif kualitatif. Instrumen yang digunakan untuk mengumpulkan data adalah angket siswa, lembar observasi kedisiplinan siswa, lembar wawancara siswa, lembar umpan balik mentor dan jurnal refleksi peneliti. Berdasarkan data dari seluruh instrumen tersebut menunjukkan bahwa pada siklus 2 ketercapaian indikator kedisiplinan bermakna baik sekali. Hal ini menunjukkan bahwa penetapan dan penerapan peraturan spesifik Raise Your Hand before Speaking dapat meningkatkan kedisiplinan siswa kelas VIII di Sekolah SMP ABC Cikarang dalam pelajaran Biologi.